The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/en6020598
|View full text |Cite
|
Sign up to set email alerts
|

Green-Roof Effects on Neighborhood Microclimate and Human Thermal Sensation

Abstract: Green roofs have been recognized as an effective sustainable design tool to mitigate urban heat island (UHI) effects. Previous studies have identified green-roof benefits in cooling and energy-conservation at the building scale, with limited exploration of the wider influence on neighborhood microclimate and human thermal comfort (HTC). This paper investigated the impacts of community-scale green-roof installation on air temperature and HTC in five typical residential neighborhoods of subtropical Hong Kong. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(120 citation statements)
references
References 28 publications
4
104
0
2
Order By: Relevance
“…[52]. However, previous studies such [52], [53] have found 1-2°C temperature reduction with green-roofs.…”
Section: E Green-roof Casementioning
confidence: 68%
“…[52]. However, previous studies such [52], [53] have found 1-2°C temperature reduction with green-roofs.…”
Section: E Green-roof Casementioning
confidence: 68%
“…International efforts against global warming are advancing, with the Paris Accord [6], The shading of the building reduces the cooling load [42,43]. The green rooftop has been investigated as a means of lowering building temperatures [44]. PV panels also provide shade and produce energy at the same time [45].…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al delineated two tree planting strategies for mitigating daytime UHI effects in a high-density urban environment [22]. In addition to the greenery at the street level, the environmental benefits of green roofs, such as alleviating UHI effects, reducing energy use, and improving microclimate and air quality, have also been extensively investigated [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%